Influence of Statins locally applied from orthopedic implants on osseous integration - Pauly, Stephan; Käppler, Kathrin; Schmidmaier, Gerhard (BMC musculoskeletal disorders, 2012)
BackgroundSimvastatin increases the expression of bone morphogenetic protein 2 (BMP-2) in osteoblasts, therefore it is important to investigate the influence of statins on bone formation, fracture healing and implant integration. The aim of the present study was to investigate the effect of Simvastatin, locally applied from intramedullary coated and bioactive implants, on bone integration using biomechanical and histomorphometrical analyses.MethodsEighty rats received retrograde nailing of the femur with titanium implants: uncoated vs. polymer-only (poly(D,L-lactide)) vs. polymer plus drug coated (either Simvastatin low- or high dosed; “SIM low/ high”). Femurs were harvested after 56 days for radiographic and histomorphometric or biomechanical analysis (push-out).ResultsRadiographic analysis revealed no pathological findings for animals of the control and SIM low dose group. However, n=2/10 animals of the SIM high group showed osteolysis next to the implant without evidence of bacterial infection determined by microbiological analysis. Biomechanical results showed a significant decrease in fixation strength for SIM high coated implants vs. the control groups (uncoated and PDLLA). Histomorphometry revealed a significantly reduced total as well as direct bone/implant contact for SIM high- implants vs. controls (uncoated and PDLLA-groups). Total contact was reduced for SIM low vs. uncoated controls. Significantly reduced new bone formation was measured around SIM high coated implants vs. both control groups.ConclusionsThis animal study suggests impaired implant integration with local application of Simvastatin from intramedullary titanium implants after 8 weeks when compared to uncoated or carrier-only coated controls.